2021
DOI: 10.1016/j.cell.2021.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Spatially confined sub-tumor microenvironments in pancreatic cancer

Abstract: Highlights d PDAC regional heterogeneity stems from sub-tumor microenvironments (subTMEs) d SubTMEs exhibit distinct immune phenotypes and CAF differentiation states d SubTMEs execute distinct tumor-promoting and chemoprotective functions d Intratumoral subTME co-occurrence links stromal heterogeneity to patient outcome

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
208
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(260 citation statements)
references
References 59 publications
15
208
1
Order By: Relevance
“…Coordination between basal/mesenchymal malignant cell states and immune responses may be a broadly relevant phenomenon given our observations in other basal-like tumors and recent work in glioblastoma ( Hara et al, 2021 ). A recent publication further supports the idea that local TME variation can influence clinical outcomes in PDAC ( Grünwald et al, 2021 ), while our work provides direct evidence that TME signals are critical drivers of malignant cell state and that cell state dictates drug sensitivity. Larger cohorts of longitudinal single-cell measurements, both spatially resolved and transcriptome-wide, from individual patients undergoing therapy are needed to fully assess variation in the TME, the kinetics of cell state plasticity, and their consequences for therapeutic response.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Coordination between basal/mesenchymal malignant cell states and immune responses may be a broadly relevant phenomenon given our observations in other basal-like tumors and recent work in glioblastoma ( Hara et al, 2021 ). A recent publication further supports the idea that local TME variation can influence clinical outcomes in PDAC ( Grünwald et al, 2021 ), while our work provides direct evidence that TME signals are critical drivers of malignant cell state and that cell state dictates drug sensitivity. Larger cohorts of longitudinal single-cell measurements, both spatially resolved and transcriptome-wide, from individual patients undergoing therapy are needed to fully assess variation in the TME, the kinetics of cell state plasticity, and their consequences for therapeutic response.…”
Section: Discussionsupporting
confidence: 85%
“…While PDAC subtyping studies have largely recovered common expression features, it remains unclear whether these bulk RNA-seq state measurements mask heterogeneity at the single-cell level, which features derive from malignant versus non-malignant cells, and how well they are recapitulated in laboratory models. Moreover, the PDAC tumor microenvironment (TME) includes numerous non-malignant immune and stromal cell types ( Balachandran et al, 2019 ; Bernard et al, 2019 ; Elyada et al, 2019 ; Grünwald et al, 2021 ; Ligorio et al, 2019 ), but their variation across different sites of disease and their effects on malignant cell state and therapeutic response is not well characterized. Given the lack of mutational biomarkers for PDAC, understanding how cell state is shaped by the local TME and whether cell state can be used as a tractable biomarker for therapy selection remains of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting aspect of CAF heterogeneity is their discrete spatial localization in the PDAC microenvironment. Grünwald et al [54] characterized this heterogeneity in the context of overall stromal heterogeneity in resected human PDAC specimens, as well as in biopsies from metastatic PDAC lesions. The authors classified the PDAC TME into two main, histologically distinguishable entities-the 'Deserted' TME, with an acellular appearance and thin, spindle-shaped fibroblasts, and the 'Reactive' TME, with active fibroblasts and abundant inflammatory infiltrate; an intermediate TME state between these two could also be identified.…”
Section: Caf Heterogeneitymentioning
confidence: 99%
“…The next wave of studies anticipated in the near future will undoubtedly shed further light on which model systems and assays carry the greatest predictive power. Several published studies have described the composition and transcriptional evolution of PDAC organoids and primary tumors at a single-cell resolution [57,71,74,101]. However, these studies have not yet revealed the extent to which subclonal resistance mechanisms contributing to tumor escape occur and could be identified at baseline or emerge as a response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the total ductal cell-type-enriched proteome derived from pancreatic cancer tissue differs markedly from the corresponding ductalenriched proteome derived from adjacent non-malignant pancreatic tissue [68]. The tumor stroma may act as both a physical barrier impairing drug delivery [69] and play a key role in the development of biochemical drug resistance [57,59,70,71]. Specific CAF subsets were also found to associate with immunotherapy responses [72,73].…”
Section: Co-culturesmentioning
confidence: 99%